1999
DOI: 10.1046/j.1365-2869.1999.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing in a predominantly African‐American pediatric population

Abstract: SUMMARYThe goal of this study was to characterize sleep and respiratory parameters in children with sleep-disordered breathing (SDB) as compared to children without SDB. Data are from 198 children and adolescents referred for sleep center evaluation, 128 of whom were diagnosed with SDB. In children with SDB, obesity (> 95% wgt for age) was more common than being severely underweight (< 5% wgt for age), but only the older children with SDB were heavier than age-matched normal sleepers. Children with SDB had inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 16 publications
1
51
1
2
Order By: Relevance
“…Consistent with the literature [5,6,21,32] we found that African-American children were 3.13 times more likely to have OSA and 4.9 times more likely to have asthma than other children. There was also an increased risk of OSA in children on medical assistance compared to those with private insurance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the literature [5,6,21,32] we found that African-American children were 3.13 times more likely to have OSA and 4.9 times more likely to have asthma than other children. There was also an increased risk of OSA in children on medical assistance compared to those with private insurance.…”
Section: Discussionsupporting
confidence: 91%
“…Sleep disturbances as a consequence of nocturnal asthma have been reported in children [3], but there is only a small body of literature describing polysomnographic (PSG) features in asthma. Respiratory illnesses such as asthma, which affects 7.5-10% of American children, and atopy are reported to be risk factors for the development of OSA [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…29 However, the etiology and incidence of childhood OSA are evolving to resemble adult disease with the increasing prevalence of childhood obesity. 1,[30][31][32][33] In adults, OSA is linked to obesity. [34][35][36][37][38] In a prospective evaluation of adults, NC corrected for height was actually a better predictor of OSA than symptoms or general obesity, as assessed by body mass index (BMI).…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Additional covariates such as body positions during sleep, obesity, gender, and ethnic origin may also be important; these covariates were not all quantitated in the Koomson study. [24][25][26][27] Regardless of the flaws in the Koomson study, they have turned over a rock and now new interesting questions have been raised. We challenge them or other investigators to perform a prospective study that controls for anesthetic technique, surgeon, opioid use, body habitus, ethnic origin, and surgical technique and collects all oximeter and apnea data continuously while also tracking the child's sleep position.…”
mentioning
confidence: 99%
“…[20][21][22][23] Des covariables supplémentaires, comme la position du corps pendant le sommeil, l'obésité, le sexe et l'origine ethnique pourraient aussi être importantes, mais elles ne sont pas quantifiées dans l'étude de Koomson. [24][25][26][27] Mis à part les défauts de l'étude, les auteurs ont mis au jour de nouveaux faits et soulevé de nouvelles questions fort intéressantes. Le défi leur est lancé, ainsi qu'à d'autres chercheurs, de réaliser une étude prospective qui tienne compte de la technique anesthésique, du chirurgien, de l'usage d'opioïdes, de la morphologie corporelle, de l'origine ethnique et de la technique chirurgicale, et qui recueille toutes les données de l'oxymétrie et de l'apnée de façon continue tout en notant la position de l'enfant pendant le sommeil.…”
unclassified